PENGARUH KUALITAS PRODUK, CITRA MEREK DAN WORD OF MOUTH TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN PADA MAHASISWA ESA UNGGUL PENGGUNA IPHONE - Sugiyanto; Edo Maryanto (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2021)
The purpose of this study was to determine the effect of product quality, brand image and word of mouth on repurchase interest through consumer satisfaction in Esa Unggul Student Iphone users. This type of research is quantitative research with causal associative research. The population in this study were 170 regular and parallel active students at Esa Unggul University, Faculty of Economics, Citra Raya, which were taken using the purposive sampling method. Data testing was carried out using the validity test, reliability test, and path analysis methods. Based on the results of the study, several conclusions can be drawn as follows: 1) Product Quality, Brand Image, Word of Mouth variables have a positive and significant effect on consumer satisfaction in students of the economics faculty of Esa Unggul University; 2) Variables of Product Quality, Brand Image, Word of Mouth, and Consumer Satisfaction have a positive and significant effect on repurchase interest in students of the economics faculty of Esa Unggul University; 3) Product Quality and Brand Image variables have a positive and significant influence on repurchase intention but consumer satisfaction does not mediate; and 4) Word of Mouth variable has a positive and significant effect on repurchase intention by mediating consumer satisfaction.